PENGARUH STRESS KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA PADA DINAS PENDIDIKAN KOTA MEDAN - Farisi, Salman; Pane, Ilyas Hadi (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
This study aims to determine the effect of job stress and compensation on job satisfaction at the Medan City Education Office. This research is a quantitative study using questionnaire data collection techniques. The population in this study amounted to 108 employees and the sample taken was 85 employees of the Medan City Education Office. The sampling technique used was purposive sampling technique. The analytical method used is multiple linear regression analysis. The results showed that the value of Job Stress T = 6.187 then obtained Tcount>Ttable or 6.187> 1,663 , a significant value of 0.000 <0.05 so that job stress has a positive and significant effect on job satisfaction. The value of Compensation T = 4.808, then it is obtained that t count> T table or 4.808> 1,663 , a significant value of 0.000 <0.05 so that compensation has a positive and significant effect on job satisfaction. The value of Fcount of job stress and compensation is 67.567, so it is obtained Fcount>Ftable or 67.567> 2,716 , a significant value of 0.000 <0.05, the value of job stress and compensation has a positive and significant effect on job satisfaction at the Medan City Education Office.